Situational crime prevention and worldwide piracy: a cross‑continent analysis - Mandala, Marissa (2015)
Relying on situational crime prevention perspective, this study compares successful and unsuccessful pirate attacks reported to the International Maritime Bureau (IMB) from the year 2000 through 2013 (n = 4,902). The study builds upon the recent work of Shane and Magnuson in Justice Quarterly, pp 1–26 (2014), which found various SCP techniques effectively prevented piracy attacks on a global level. The current study builds upon these findings by testing whether the global effect of SCP is consistent across individual continents. A series of mixed-effects logistic regression models and follow-up likelihood ratio tests were incorporated to explore the research question. In each model, SCP techniques were associated with unsuccessful piracy attacks on a global level. When considered individually, SCP techniques were equally effective in each continent. However, the use of multiple techniques classified within the increased effort technique of SCP was associated with increased likelihood of unsuccessful attacks in only 3 (South East Asia, Far East, and Rest of the World) of the 6 continents included in this study. The implications of these findings are discussed